1990
DOI: 10.1073/pnas.87.22.9052
|View full text |Cite
|
Sign up to set email alerts
|

Identification and structural analysis of residues in the V1 region of CD4 involved in interaction with human immunodeficiency virus envelope glycoprotein gp120 and class II major histocompatibility complex molecules.

Abstract: The human CD4 molecule binds both human immunodeficiency virus envelope protein gpl20 and class H major histocompatibility complex (MHC) molecules. We have studied a series of mutants in the region of amino acids 42-49 of CD4 for their ability to bind gpl20, to interact with class II MHC, to enhance T-cell activation, and to bind a panel of anti-CD4 antibodies. The mutation Q40P (Gln4O -Pro) and the deletion d42-49 were found to disrupt most antibody epitopes in the V1 domain of CD4, suggesting major conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…2, 65% vs. 0%6 of specific binding). Partial reduction in adhesion of B cells to a CD4 cDNA-transfected hybridoma containing F43L was also observed by others (43). Leucine, like phenylalanine, has a y-branched side chain and therefore is more structurally related to phenylalanine than isoleucine with its P-branched side chain.…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…2, 65% vs. 0%6 of specific binding). Partial reduction in adhesion of B cells to a CD4 cDNA-transfected hybridoma containing F43L was also observed by others (43). Leucine, like phenylalanine, has a y-branched side chain and therefore is more structurally related to phenylalanine than isoleucine with its P-branched side chain.…”
Section: Methodsmentioning
confidence: 68%
“…Thus, other parts of domains 1 and 2 are involved in the interaction with class II molecules. Reports by Bowman et al (43) and Fleury et al (29) also showed interference from changes in strands C' and C" of domain 1. These papers demonstrate negative effects of proline substitutions at either position 40 Sites.…”
Section: Methodsmentioning
confidence: 97%
“…With the resolution of class I1 structure by X-ray crystallography and the observation that class I1 may exist as dimers of the up heterodimers, it was suggested that the Interactions of T-cells with major histocompatibility complex CD4 binding residues of the P 2 domain of one class I1 heterodimer lie in close apposition to the az domain of the other heterodimer [4,741. This raised the possibility that CD4 may stabilize the 'dimer of dimers' and promote the aggregation of TcRs on the surface of the activating T-cell, especially if CD4 itself has a propensity to dimerize [75, 761. It was evident from domain shuffling data [69], CD4 mutagenesis [63,[77][78][79][80][81][82] and antibody binding studies [62, 64, 831 that more than one region within the CD4 molecule is involved in class I1 binding. The data described in this section exploit the species barrier between mouse class I1 molecules and human CD4 [67][68][69]841 to study the role of the a2 domain in T-cell recognition by introducing the a2 domain of murine H-2E into HLA-DR1.…”
Section: Contribution Of the Class II Az Domain To T-cell Recognitionmentioning
confidence: 99%
“…As a key receptor on cell membranes, CD4 is known to physically interact with GP120 (427)(428)(429)(430)(431)(432) and Vpu (14,19,433). Due to the flexible nature of HIV-1 Env, the closed and open conformations of Env drive the dynamic binding of Env to CD4, coreceptors, and antibodies (56,434).…”
Section: Vpu-cd4-gp120 Env Associationmentioning
confidence: 99%